2022
DOI: 10.3390/cancers14174133
|View full text |Cite
|
Sign up to set email alerts
|

Digital and Interactive Health Interventions Minimize the Physical and Psychological Impact of Breast Cancer, Increasing Women’s Quality of Life: A Systematic Review and Meta-Analysis

Abstract: Digital and interactive health interventions (DIHIs), such as virtual-reality-based therapy (VRBT) and smartphone-app-based therapy (SABT), may be useful for reducing the impact of the signs and symptoms of breast cancer (BC) in women. The aim of this meta-analysis was to explore the effect of DIHIs on improving pain, anxiety, depression, quality of life (QoL), and upper extremity (UE) disability-related lymphedema in women with BC. Methods: We searched PubMed Medline, Web of Science, Scopus, CINAHL, Physiothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…Virtual reality-based early rehabilitation (VRBR) is based on the use of virtual reality devices that allow the patient to be introduced into a virtual environment that feels similar to real-world using a computer, virtual reality glasses, or a game station, allowing interaction with this virtual environment and their objects through your own hands or joystick [20,21]. Virtual reality systems require two characteristics: immersion and presence [22].…”
Section: Introductionmentioning
confidence: 99%
“…Virtual reality-based early rehabilitation (VRBR) is based on the use of virtual reality devices that allow the patient to be introduced into a virtual environment that feels similar to real-world using a computer, virtual reality glasses, or a game station, allowing interaction with this virtual environment and their objects through your own hands or joystick [20,21]. Virtual reality systems require two characteristics: immersion and presence [22].…”
Section: Introductionmentioning
confidence: 99%
“…This current and previous reviews [35,37] suggest that digital interventions promoting symptom monitoring and support patients to self-manage symptoms have been shown to improve outcomes in cancer patients. Additionally, these interventions can facilitate early detection and intervention by promoting regular monitoring via self-assessment tools and symptom tracking.…”
Section: So Can Wbis Manage Chronic Pain?mentioning
confidence: 87%
“…Studies have utilised these interventions to help manage chronic post-treatment symptoms in breast cancer survivors. These include encouraging patients to exercise, adhere to endocrine treatments, and cope with longer term outcomes from adjuvant treatments including anxiety and depression, loss of functionality, lymphoedema and reduced quality of life [32][33][34][35][36].…”
Section: Harnessing Technology Advances In Pain Managementmentioning
confidence: 99%
“…The large number of studies ( n = 43) included in this review is another strength, increasing the reliability of the treatment effects identified. In contrast, previous reviews have included around 15–20 studies each 9,14,22,82–84 . The meta‐analysis allowed for a more robust evaluation of efficacy and comparison between guided and non‐guided interventions, thus ensuring generalisability and better guidance of future research and practice.…”
Section: Discussionmentioning
confidence: 99%